(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Postoperative mediastinal bleeding in patients undergoing cardiac surgery is still one of the most common complications. Objective: This study was intended to investigate the efficacy of topical tranexamic acid in reducing postoperative bleeding after OPCAB surgery. Methodology: This non-randomized, double blinded, clinical trial was conducted in the Department of Cardiac Surgery at National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh during January 2014 to December 2015 for a period of two (2) years. Patients undergone CABG after fulfilling the inclusion and exclusion criteria was recruited for this study. They were assigned in two groups 30 patients in tranexamic acid group (Group 1) and 30 patients in placebo group (Group 2). On completion of the grafting, before closure of the sternum tranexamic acid (2.5 g/25 mL) or placebo (25 mL of saline) diluted in 100 mL of warm saline (37° C) was instilled into the pericardial cavity including the mediastinal tissues and left for 5 minutes. Then it was cleared out by wall sucker and sternum was closed. Result: There was no significant difference in baseline demographic data, basic clinical characteristics and preoperative coagulation profile between the 2 groups (P>0.05). Total mediastinal bleeding in group 1 and group 2 patients were 421.67±70.32 vs 593.33±77.38 ml (p<0.001). In case of, whole blood transfusion in group 1 and group 2 patients were 0.87±0.0.73 units and 1.77±0.57 units respectively (p<0.001). No patient required reoperation for bleeding and there was no incidence of prolonged ventilation, MI, thromboembolism, DVT or CVA in any of the patients in either group. Conclusion: In conclusion the efficacy of topical tranexamic acid is helpful for reducing postoperative bleeding after OPCAB surgery. Journal of National Institute of Neurosciences Bangladesh, 2016;2(2): 79-83